Enhancing business performance through Maslahah relationship marketing: The mediating role of entrepreneurial orientation - Wahyudi, Wahyudi; Sulistyo, Heru; Wikaningrum, Tri; Heridiansyah, Jefri (Edelweiss Applied Science and Technology, 2025)
This study examines the mediating role of Maslahah Relationship Marketing (MRM), an Islamic value-based marketing approach, in the relationship between Entrepreneurial Orientation (EO) and Business Performance (BP) within the Indonesian manufacturing sector. Grounded in Resource Advantage Theory (RAT), MRM is conceptualized as a multidimensional construct comprising rational trust, consistent commitment, effective communication, holistic competence, and holistic empathy. Data were collected from 240 respondents across various managerial levels at PT Perkebunan Nusantara I Regional 3 in Central Java, Indonesia, using a stratified random sampling method, with a sample size of 181 respondents. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to test the proposed model. Results indicate that EO, through proactiveness and innovativeness, positively influences MRM components, which in turn significantly enhance BP. This study contributes to the literature by introducing MRM as a novel framework that integrates Islamic values into relationship marketing, offering practical implications for fostering sustainable business relationships in Muslim-majority markets.